2006
DOI: 10.2337/diacare.29.03.06.dc05-01467
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Retention and Vascular Effects of Rosiglitazone in Obese, Insulin-Resistant, Nondiabetic Subjects

Abstract: OBJECTIVE -The use of thiazolidinedione (TZD) derivatives is associated with fluid retention, especially when combined with insulin. Because TZDs improve the metabolic effect of insulin, they may also reverse the blunted vascular response to insulin. We hypothesize that improvement of the action of insulin on vascular tone or permeability is the key mechanism of TZD-related fluid retention.RESEARCH DESIGN AND METHODS -In a randomized, double-blind, placebocontrolled, cross-over study in 18 obese, nondiabetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
4
16
1
Order By: Relevance
“…The drugs also improve beta‐cell function and reduce blood pressure [ 82 ]. However, the use of TZDs is often associated with an adverse effect: fluid retention and peripheral edema, especially when used in combination with insulin [ 59 ]. In many cases, especially when patients have congestive heart disease, the risk of developing pulmonary edema limits its clinical utility [ 39 ].…”
Section: Clinical Aspects Related To Insulin Resistance and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs also improve beta‐cell function and reduce blood pressure [ 82 ]. However, the use of TZDs is often associated with an adverse effect: fluid retention and peripheral edema, especially when used in combination with insulin [ 59 ]. In many cases, especially when patients have congestive heart disease, the risk of developing pulmonary edema limits its clinical utility [ 39 ].…”
Section: Clinical Aspects Related To Insulin Resistance and Therapymentioning
confidence: 99%
“…On the other hand, peripheral microvascular leakage may contribute, at least partially, to the accumulation of fluid in tissues. The peripheral effects of TZDs are thought to occur through the augmented insulin effects on vasodilation, capillary recruitment, and hyperpermeability [ 59 , 67 , 69 ]. In addition, Rosiglitazone has been shown to increase transendothelial albumin flux in human pulmonary artery endothelial cells [ 39 ].…”
Section: Clinical Aspects Related To Insulin Resistance and Therapymentioning
confidence: 99%
“…This may be due to a combined effect of thiazolidinediones and insulin or to complications accompanying longstanding diabetes [9]. In a previous study in insulin-resistant people without diabetes, we found no evidence for adverse vascular effects of the combined use of rosiglitazone and insulin [20], suggesting that it is not insulin itself but probably complications associated with longstanding diabetes that render patients prone to oedema formation. Autonomic neuropathy is a typical complication of longstanding diabetes [21, 22].…”
Section: Introductionmentioning
confidence: 74%
“…It could be due to up-regulation of the epithelial sodium channel [68, 69], increased sympathetic nervous system activity or altered endothelial permeability [70, 71]. Fluid retention accounts for at least 75% of body weight gain in patients receiving TZDs [72, 73], and furthermore contributes to the increased incidence of congestive heart failure (see below).…”
Section: Fluid Retentionmentioning
confidence: 99%